2012
DOI: 10.1097/aog.0b013e318242032a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Best-Practice Alert on the Rate of Influenza Vaccination of Pregnant Women

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 5 publications
3
40
0
Order By: Relevance
“…19 The use of the electronic medical record has been shown to be associated with increased influenza vaccination rates in several high-risk groups. [20][21][22] Klatt and Hopp recently examined the association of a best-practice alert implementation and pregnant women's acceptance of the influenza vaccine. They noted a significant increase in influenza immunization rates, from 42% to 61% after the best-practice alert was instituted.…”
Section: Discussionmentioning
confidence: 98%
“…19 The use of the electronic medical record has been shown to be associated with increased influenza vaccination rates in several high-risk groups. [20][21][22] Klatt and Hopp recently examined the association of a best-practice alert implementation and pregnant women's acceptance of the influenza vaccine. They noted a significant increase in influenza immunization rates, from 42% to 61% after the best-practice alert was instituted.…”
Section: Discussionmentioning
confidence: 98%
“…Despite strong evidence showing the importance of recommendations by care providers, less than half of pregnant women in 2 recent US studies reported receiving this advice. 22,23 Studies evaluating the efficacy of provider-focused reminders to offer vaccination to pregnant patients have been successful at significantly increasing vaccination rates, 25,26 which suggests that this is a promising strategy. In contrast, a randomized study involving patient reminders sent via text messaging failed to im prove vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits were also demonstrated in a study of "best practice alerts" in charts that also use a pre-and post-intervention analysis. 75 A computer decision support algorithm that aided in identifying women needing immunization was found to be an effective intervention in a hospital-based clinic, 76 and opt-in and standing orders for vaccination have also been shown to be effective. 77 Patient 78,79 and physician education 74,78 have also been shown to increase vaccine uptake rates, although several of the previously cited chart alert interventions were implemented after failure of physician education programs.…”
Section: Interventionsmentioning
confidence: 99%
“…77 Patient 78,79 and physician education 74,78 have also been shown to increase vaccine uptake rates, although several of the previously cited chart alert interventions were implemented after failure of physician education programs. 75,76 A "teach back" method of providing health information was assessed in Jamaica, and its success was associated with health literacy which was closely correlated with overall literacy. 80 Studies of text messaging reminders have had mixed results.…”
Section: Interventionsmentioning
confidence: 99%